Simulation of size effects on the optical properties of KTP nanoparticles - Nematollah Abdi Valikchali; Majid Jafar Tafreshi; Fatemeh Shariatmadar Tehrani (Progress in Physics of Applied Materials)
KTiOPO4 (KTP) is a non-linear optical crystal with high non-linear optical coefficients and an optical damage threshold that has wide applications in optical devices. The optical properties of KTP nanoparticles are critical in nanotechnology. This study employs COMSOL Multiphysics software and the finite element method (FEM) in order to examine the effects of particle size (10 to 100 nm) on the optical properties of spherical KTP nanoparticles, including refractive index dispersion, scattering cross-section, band gap energy, and cut-off wavelength. The obtained results were compared with the available experimental data. The results of this research showed that the refractive index dispersion and scattering cross-section for KTP nanoparticles follow the FEM model and Mei's theory for spherical nanoparticles. For radiated light with a specific wavelength, decrease in the size of KTP nanoparticles causes a decrease in the scattering cross-section, refractive index, and absorption edge wavelength. By decreasing the particle size from 100 nm to 50 nm, the refractive index remained almost constant at 1.81 and decreased slightly with further decrease in particle size to 20 nm. Also, reducing the particle size below 20 nm decreased the refractive index to 1.80. The band gap energy of KTP nanoparticles increased from 3.9 eV to 6.27 eV as the particle size decreased from 100 nm to 10 nm. However, a significant increase in band gap energy was observed when particle size decreased from 20 nm to 10 nm. The results of the simulation work were found to be consistent with the previous reports.